Why Don't We Move Faster? Parkinson's Disease, Movement Vigor, and Implicit Motivation - Mazzoni, Pietro; Hristova, Anna; Krakauer, John W (The Journal of neuroscience, 2007)
People generally select a similar speed for a given motor task, such as reaching for a cup. One well established determinant of movement time is the speed–accuracy trade-off: movement time increases with the accuracy requirement. A second possible determinant is the energetic cost of making a movement. Parkinson's disease (PD), a condition characterized by generalized movement slowing (bradykinesia), provides the opportunity to directly explore this second possibility. We compared reaching movements of patients with PD with those of control subjects in a speed–accuracy trade-off task comprising conditions of increasing difficulty. Subjects completed as many trials as necessary to make 20 movements within a required speed range (trials to criterion, N c ). Difficulty was reflected in endpoint accuracy and N c . Patients were as accurate as control subjects in all conditions (i.e., PD did not affect the speed–accuracy trade-off). However, N c was consistently higher in patients, indicating reluctance to move fast although accuracy was not compromised. Specifically, the dependence of N c on movement energy cost (slope S N ) was steeper in patients than in control subjects. This difference in S N suggests that bradykinesia represents an implicit decision not to move fast because of a shift in the cost/benefit ratio of the energy expenditure needed to move at normal speed. S N was less steep, but statistically significant, in control subjects, which demonstrates a role for energetic cost in the normal control of movement speed. We propose that, analogous to the established role of dopamine in explicit reward-seeking behavior, the dopaminergic projection to the striatum provides a signal for implicit “motor motivation.”